STUDY OF IONIC LIQUID IMPREGNATED SUPPORT FOR C02 ADSORPTION - MAT DAGANG, NURUL SAFIAH (2016)
Ionic liquids (ILs) are getting more attention in the research world due to its green properties such as thermally and chemically stable, non-volatile, and can be tuned or designed for a particular application. ILs have been proven to give promising results in C02 capture applications. However, the viscosity of ILs is high which can limit the mass transfer of molecules in the ILs. The use of water to reduce the viscosity however leads to ILs loss due to evaporation and corrosion problem